2004
DOI: 10.1097/00006231-200405000-00003
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET, somatostatin receptor scintigraphy, and CT in metastatic medullary thyroid carcinoma: a clinical study and an analysis of the literature

Abstract: Overall, CT is similar or better than PET in our patients (dependent on the standard) while SRS is inferior to both other techniques. Our data are in agreement with publications that consider CT superior to PET in the diagnosis of metastatic MTC while other studies show superiority of PET. However, a combination of CT and PET seems to be the most appropriate non-invasive diagnostic approach in patients with MTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…A possible explanation for this low 18 F-FDG PET/CT sensitivity (17%) in our series when compared to those reported in the literature (30-95%) could be related to the significant number of MTC [8,9,11,[13][14][15][23][24][25][26][27][28][29][30][31][32][33]. Nevertheless, 18 F-FDG PET/CT may provide useful information in patients with more aggressive disease, as demonstrated in patient 4 in whom it detected multiple liver lesions that were missed on functional PET/CT with the other two tracers, as well as two additional locoregional lymph nodes.…”
Section: Discussionmentioning
confidence: 83%
“…A possible explanation for this low 18 F-FDG PET/CT sensitivity (17%) in our series when compared to those reported in the literature (30-95%) could be related to the significant number of MTC [8,9,11,[13][14][15][23][24][25][26][27][28][29][30][31][32][33]. Nevertheless, 18 F-FDG PET/CT may provide useful information in patients with more aggressive disease, as demonstrated in patient 4 in whom it detected multiple liver lesions that were missed on functional PET/CT with the other two tracers, as well as two additional locoregional lymph nodes.…”
Section: Discussionmentioning
confidence: 83%
“…Hoegerle et al [26] reported an overall sensitivity of 63% for 18 F-DOPA PET in 11 patients with MTC, which was lower than that observed with c.e.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 85%
“…Their results suggest that CT is similar to or better than PET, whereas SRS is inferior to the two other techniques. The authors conclude that a combination of CT and PET seems to be the most appropriate noninvasive diagnostic approach in patients with MTC [19]. Additionally, some groups have suggested that hybrid scanners such as PET/CT could help localize metastases in the presence of low or normal calcitonin levels because calcitonin should be undetectable in the absence of tumor [20].…”
Section: Discussionmentioning
confidence: 99%